Exploration of faecal prevalence of internal parasite eggs in children and dogs from three rural high-altitude hamlets in the Peruvian northern Andes. - Cuzcano-Anarcaya, J.L.C (2025)
This study aimed to identify and determine the prevalence of intestinal parasites through faecal egg detection in children and dogs from three rural hamlets - La Chorrera, Cruz Pampa, and Chugurmayo - located in the Sorochuco district, Celendín province, Cajamarca region, Peru, at an altitude exceeding 3,400 meters above sea level. Faecal samples were collected from school-aged children and domestic dogs and analysed using direct smear, natural sedimentation, Faust, and Sheather techniques. Parasitic infection was detected in 59.80% of children (95% CI: 50.29–69.32) and 55.00% of dogs (95% CI: 44.10–65.90). No statistically significant differences in prevalence were observed between hamlets (p = 0.630). Among children, the highest prevalence was noted in males aged >6 to 9 years; in dogs, it was observed in males aged 0 to 1 year. However, age and sex were not significantly associated with infection in either group (p > 0.05). Parasitic stages identified in children included Giardia spp., Hymenolepis spp., Fasciola hepatica, Ascaris lumbricoides, and Diphyllobothrium spp. In dogs, Giardia spp., Ancylostomatidae, Sarcocystis spp., Toxocara spp., and Taenia spp. were found. One parasite - Giardia spp. - were common to both species, although no significant overall correlation of infection between children and dogs was observed (p > 0.05). These findings highlight the need for enhanced epidemiological surveillance, medical attention, and further research in these underserved rural communities. Increased awareness and integrated public health efforts are essential to address the burden of parasitic infections in these high-altitude areas.